If we build it, they will come: Caregiver decision to use an accessible outpatient psychiatric service for children and adolescents in Nigeria. (June 2021) - Kang, Ezer; Omigbodun, Olayinka; Oduguwa, Adeola; Kim, Woojae; Qin, Lu; Ogunmola, Olusegun; Akinkuotu, Folasade; Derenoncourt, Meghan; Abdurahman, Haleem; Adejumo, Olurotimi; Lawal, Kehinde; Bella-Awusah, Tolulope
Abstract: Objective: If child and adolescent psychiatric (CAP) services were accessible in lower-middle-income countries (LMIC) such as Nigeria, what individual and socio-cultural factors would influence caregivers' willingness to use these services when they are needed? Methods: To address this question, we conducted structured interviews with a stratified random sampling of 442 adult caregivers of children aged 5 to 19-years who lived within 10 km of an established CAP outpatient service in Ibadan, Nigeria. Results: Based on structural equation modeling, our cross-sectional findings indicated that caregivers were generally willing to use the accessible outpatient CAP service for a narrow range of overtly disruptive and developmentally atypical child behavior. However, their decisions were not influenced by their recognition of child and adolescent mental health (CAMH) conditions, competing life stressors, caregiver wellness, nor stigma as we had initially hypothesized. Rather caregivers pragmatically considered a range of approaches to address CAMH concerns. Post-hoc hypotheses confirmed that caregivers' beliefs about etiology and treatment effectiveness for CAMH conditions shaped their help-seeking decisions and stigmatization of CAP services. Specifically, caregivers who attributed CAMH conditions to physical causes regarded biomedical interventions as the most effective treatment while spiritual interventions were deemed to be the least effective. Conclusions: Taken together our results suggested that caregivers were receptive and willing to use outpatient psychiatric services for their children. However, their beliefs about the etiology and treatment effectiveness of CAMH conditions shaped how they intended to engage the services. These findings underscored the importance of scaling up a broader spectrum of accessible complementary CAMH intervention and prevention services in Nigeria that extend beyond indigenous or biomedical models. In doing so caregivers will come. Highlights: Caregivers will use accessible child and adolescent psychiatric (CAP) services. Caregivers in Nigeria use CAP services for narrowly defined deviant child behaviors. They believe a wide range of approaches can address child mental health problems. Beliefs about mental illness etiologies shape appraisals of effective approaches. Treatment/prevention should extend beyond siloed indigenous and biomedical models.